Novel lubricating oil composite additive, preparation method thereof and lubricating oil

A novel lubricating oil composite additive with ionic liquids and metal compound nanomaterials addresses dispersion and stability issues, enhancing lubrication performance and wear resistance in high-temperature conditions.

CN119242364APending Publication Date: 2025-01-03HENAN HONGCHENG NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411368192.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Nanoscale inorganic metal compounds in lubricating oils face challenges in even dispersion and stability, while ionic liquids offer excellent anti-wear and friction-reducing properties but their combined use with nanoscale inorganic metal compounds is insufficiently researched.

Method used

A novel lubricating oil composite additive comprising an ionic liquid with a long-chain fatty acid ligand-connected metal compound nanomaterial, specifically ZnS, CuS, PbS, CuO, MoS2, ZnO, or PbO nanomaterials, is developed, with a mass ratio of 0.5-2:1, and prepared through specific synthesis steps.

Benefits of technology

The additive enhances lubrication performance by improving wear resistance and reducing friction, maintaining stability in high-temperature and oxidative environments, and ensuring compatibility with base oils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066834480000081
    Figure BDA0005066834480000081
  • Figure BDA0005066834480000091
    Figure BDA0005066834480000091
Patent Text Reader

Abstract

The invention provides a novel lubricating oil composite additive, a preparation method thereof and lubricating oil, the novel lubricating oil composite additive comprises an ionic liquid and a metal compound nanometer material, and the surface of the metal compound nanometer material is connected with a long-chain fatty acid ligand. The ionic liquid provided by the invention not only can be used as an additive of the lubricating oil, but also can play a role in dispersing the metal compound nano-material, so that the stability and the like of the metal compound nano-material in base oil are improved, and the wear resistance and the like of the lubricating oil are further synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lubricating oils, and in particular to a novel lubricating oil composite additive, a preparation method thereof, and lubricating oil. Background Art

[0002] When two objects move relative to each other, the lubricant between them serves to reduce wear caused by contact. Lubricating oil is a liquid or semi-solid lubricant used on various mechanical equipment to reduce friction and protect machinery and workpieces. Its main functions in application are lubrication, auxiliary cooling, rust prevention, cleaning, sealing, and buffering. Lubricating oil generally consists of two parts: base oil and additives. Base oil is the main component of lubricating oil and determines the basic properties of lubricating oil. Additives can make up for and improve the deficiencies in the performance of base oil and impart certain new properties, making them an important component of lubricating oil. Additives are key substances for improving the performance of lubricating oil. Correct selection and addition of sufficient amount can improve the physical and chemical properties of lubricating oil, give lubricating oil special new properties, or enhance its original properties, thereby meeting actual needs.

[0003] Nanoscale inorganic metal compounds, when added to lubricating oils as lubricant additives, can improve the lubricating oil's overall lubricity, but they are difficult to evenly disperse and maintain stable over time. Although ionic liquid lubricant additives offer excellent anti-wear and friction-reducing properties, effectively improving lubricant wear resistance and reducing friction and wear, research on ionic liquids as lubricant additives remains insufficient, and reports on the combined use of ionic liquids with nanoscale inorganic metal compounds are even rarer. Therefore, there is a need for a novel lubricant additive combination. Summary of the Invention

[0004] The present application provides a novel lubricating oil composite additive, a preparation method thereof, and lubricating oil. The novel lubricating oil composite additive of the present invention has good dispersibility and high stability in lubricating oil, and can effectively improve the performance of lubricating oil.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a novel lubricant additive package, comprising an ionic liquid and a metal compound nanomaterial; wherein the surface of the metal compound nanomaterial is connected to a long-chain fatty acid ligand;

[0007] Furthermore, the metal compound nanomaterials include ZnS nanomaterials, CuS nanomaterials, PbS nanomaterials, CuS nanomaterials, MoS2 nanomaterials, ZnO nanomaterials, CuO nanomaterials, and PbO nanomaterials;

[0008] Furthermore, the long-chain fatty acid ligand is selected from fatty acid compounds having 10-24 carbon atoms;

[0009] Furthermore, the long-chain fatty acid ligand is selected from fatty acid compounds with 12-20 carbon atoms, specifically, decanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, linoleic acid, etc.

[0010] Further, the ionic liquid includes 1,8-diazabicyclo[5.4.0]undec-7-ene salt ionic liquid;

[0011] Furthermore, the 1,8-diazabicyclo[5.4.0]undec-7-ene salt ionic liquid is a 1-alkyl DBU fatty acid ionic liquid, wherein the alkyl group is an alkyl group having 6 to 18 carbon atoms, and the fatty acid is an alkyl acid having 12 to 18 carbon atoms;

[0012] Furthermore, the ionic liquid is selected from one or more of 1-octyl DBU oleic acid ionic liquid, 1-decyl DBU oleic acid ionic liquid, and 1-dodecyl DBU oleic acid ionic liquid;

[0013] Furthermore, the mass ratio of the ionic liquid to the metal compound nanomaterial is 0.5-2:1, specifically, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1;

[0014] In a second aspect, the present invention further provides a method for preparing a novel lubricating oil composite additive, comprising the following steps:

[0015] Step S1: Synthesis of ionic liquid: Alkyl halide is added to the DBU solution, and the mixture is heated for reaction. After the reaction is completed, an intermediate product 1 is obtained; the intermediate product 1 is then reacted with a fatty acid metal salt to obtain the ionic liquid;

[0016] Step S2: Synthesis of Metal Compound Nanomaterials: A soluble transition metal salt is added to a mixed solution of a long-chain fatty acid and a solvent, and then stirred for a period of time at a first reaction temperature under an inert gas atmosphere. The temperature is then raised to a second reaction temperature, and then a raw material A is added to precipitate the soluble transition metal salt. After the reaction is completed, the metal compound nanomaterial is obtained.

[0017] Step S3: mixing the ionic liquid with the metal compound nanomaterial to obtain the lubricating oil composite additive;

[0018] Wherein, the step S1 and the step S2 are performed in no particular order;

[0019] Furthermore, in step S1, the alkyl halide is selected from alkyl halide having 6 to 18 carbon atoms;

[0020] Furthermore, the alkyl halide is XR, wherein X is selected from F, Cl, Br, I, and R is selected from a C6-C18 alkyl group; preferably, R is selected from a C8-C12 alkyl group;

[0021] Specifically, it can be n-hexane chloride, n-octane chloride, n-decane chloride, n-dodecane chloride, n-tetradecane chloride, n-hexane bromide, n-octane bromide, n-decane bromide, n-dodecane bromide, n-tetradecane bromide, n-hexane iodide, n-octane iodide, n-decane iodide, n-dodecane iodide, n-tetradecane iodide, etc.;

[0022] Furthermore, the solvent of the DBU solution is selected from THF, acetone, dichloromethane, chloroform, tetrachloromethane, and 1,2-dichloroethane;

[0023] Furthermore, the fatty acid metal salt is selected from alkali metal salts of alkyl fatty acids having 6 to 18 carbon atoms;

[0024] Furthermore, the fatty acid metal salt is R1-COOM, wherein R1 is selected from a C11-C17 alkyl group, and M is selected from Li, Na, and K;

[0025] Specifically, it can be sodium decanoate, sodium dodecanoate, sodium tetradecanoate, sodium hexadecanoate, sodium octadecanoate, sodium oleate, sodium linoleate, potassium decanoate, potassium dodecanoate, potassium tetradecanoate, potassium hexadecanoate, potassium octadecanoate, potassium oleate, potassium linoleate, etc.;

[0026] Furthermore, in step S1, the specific conditions of the heating reaction are: reaction temperature is 60-80°C, and reaction time is 6-10h;

[0027] Furthermore, in the step S1, the molar ratio of the DBU to the alkyl halide is 1:1.1-1.2;

[0028] Furthermore, the molar ratio of the intermediate product 1 to the fatty acid metal salt is 1:1-1.2;

[0029] Furthermore, in step S2, the soluble transition metal salt is selected from soluble metal salts of zinc, soluble metal salts of copper, soluble metal salts of lead, and soluble metal salts of molybdenum; optionally, the soluble metal salt of zinc is selected from zinc acetate, zinc chloride, and zinc nitrate; the soluble metal salt of copper is selected from copper acetate, copper chloride, and copper nitrate; and the soluble metal salt of lead is selected from lead acetate and lead nitrate;

[0030] Furthermore, the long-chain fatty acid is selected from fatty acid compounds having 10 to 24 carbon atoms;

[0031] Furthermore, the solvent is selected from aliphatic hydrocarbons having 10 to 24 carbon atoms;

[0032] Furthermore, the raw material A is selected from n-octylphosphine solution of S, trioctylphosphine solution of S, triethanolamine, ethanolamine, ammonia water, NaOH, and KOH;

[0033] Furthermore, the metal compound nanomaterials include ZnS nanomaterials, CuS nanomaterials, PbS nanomaterials, CuS nanomaterials, MoS2 nanomaterials, ZnO nanomaterials, CuO nanomaterials, and PbO nanomaterials.

[0034] Furthermore, in step S2, stirring at the first reaction temperature for a period of time specifically comprises: stirring and reacting at 110-130° C. for 20-40 minutes;

[0035] Further, the second reaction temperature is 270-290°C;

[0036] Furthermore, the molar ratio of the soluble transition metal salt to the raw material A is 1:1-2;

[0037] Furthermore, in step S3, the mass ratio of the ionic liquid to the metal compound nanomaterial is 0.5-2:1; and the specific conditions for mixing the ionic liquid and the metal compound nanomaterial are: stirring and mixing at 70-90° C. for 1-3 hours.

[0038] In a third aspect, the present invention further provides a lubricating oil comprising a base oil and the novel lubricating oil composite additive, or comprising a base oil and the novel lubricating oil composite additive prepared by the above preparation method;

[0039] Furthermore, the content of the novel lubricating oil composite additive in the lubricating oil is 0.01wt% to 0.1wt%, specifically, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%,

[0040] 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%;

[0041] Furthermore, the base oil includes mineral base oil, synthetic base oil and vegetable oil base oil; preferably, the synthetic base oil is selected from PAO-4, PAO-6, PAO-8, PAO-10 and the like.

[0042] Compared to the prior art, the present application provides a novel lubricant composite additive, a preparation method thereof, and a lubricant. The novel lubricant composite additive comprises an ionic liquid and a metal compound nanomaterial, wherein the surface of the metal compound nanomaterial is connected to a long-chain fatty acid ligand. The ionic liquid provided in the present application can not only be used as a lubricant additive to effectively improve the wear resistance of the lubricant and reduce friction and wear, but can also maintain good lubrication performance in high-temperature and oxidative environments. Moreover, because the ionic liquid provided in the present application contains long-chain alkyl chains, it is highly compatible with the metal compound nanomaterial, thereby dispersing and stabilizing the metal compound nanomaterial, further synergistically improving the wear resistance of the lubricant. DETAILED DESCRIPTION

[0043] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In the description of the present application, it should be understood that "and / or" describes the association relationship of associated objects and indicates that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In the present application, "at least one" refers to one or more, and "a plurality" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0045] The present application will be described in detail below through specific examples. The following examples are only some examples of the present application and cannot be used to limit the present application.

[0046] Example 1

[0047] This embodiment provides a lubricating oil additive package, which is prepared by the following steps:

[0048] (1) Synthesis of 1-octyl DBU oleic acid ionic liquid: 0.1 mol DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) and 20 mL THF were added to a three-necked flask, and 0.11 mol of n-octane bromide was slowly added dropwise at about 60°C. After the addition was complete, the temperature was raised to about 70°C and stirred for 8 hours. After the reaction was completed, the solvent was evaporated and the crude product was dissolved in 50 ml of distilled water. The product was then washed three times with ether, evaporated and dried under vacuum to obtain 1-octyl DBU bromide ionic liquid, which was then reacted with sodium oleate to obtain 1-octyl DBU oleic acid ionic liquid.

[0049] (2) Synthesis of ZnS Nanomaterials: 0.4 mmol zinc acetate, 1 mL oleic acid, and 10 mL octadecene were placed in a three-necked flask and mixed at 120°C under vacuum for 30 min. The mixture was then heated to 280°C under an argon atmosphere. 0.4 mmol S in n-octylphosphine solution was injected into the reaction system and allowed to mature for 20 min. The mixture was then precipitated and purified three times using n-heptane as solvent and ethanol as non-solvent to obtain oleic acid-stabilized ZnS nanomaterials.

[0050] (3) 10 g of 1-octyl DBU oleic acid ionic liquid and 10 g of ZnS nanomaterial were stirred and mixed at 80° C. for 2 h to obtain a lubricating oil composite additive.

[0051] Example 2

[0052] The only difference from Example 1 is that 8 g of 1-octyl DBU oleic acid ionic liquid and 12 g of ZnS nanomaterial are stirred and mixed at 80° C. for 2 h to obtain a lubricating oil composite additive.

[0053] Example 3

[0054] The only difference from Example 1 is that 12 g of 1-octyl DBU oleic acid ionic liquid and 8 g of ZnS nanomaterial are stirred and mixed at 80° C. for 2 h to obtain a lubricating oil composite additive.

[0055] Example 4

[0056] This embodiment provides a lubricating oil additive package, which is prepared by the following steps:

[0057] (1) Synthesis of 1-decyl DBU oleic acid ionic liquid: 0.1 mol DBU and 20 mL THF were added to a three-necked flask, and 0.11 mol of n-decane bromide was slowly added dropwise at about 60°C. After the addition was complete, the temperature was raised to about 70°C and stirred for 8 hours. After the reaction was complete, the solvent was evaporated and the obtained crude product was dissolved in 50 ml of distilled water. The product was then washed three times with ether, evaporated and dried under vacuum to obtain 1-decyl DBU bromide ionic liquid. The product was then reacted with sodium oleate to obtain 1-decyl DBU oleic acid ionic liquid.

[0058] (2) Synthesis of ZnS Nanomaterials: 0.4 mmol zinc acetate, 1 mL oleic acid, and 10 mL octadecene were placed in a three-necked flask and mixed at 120°C under vacuum for 30 min. The mixture was then heated to 280°C under an argon atmosphere. 0.4 mmol S in n-octylphosphine solution was injected into the reaction system and allowed to mature for 20 min. The mixture was then precipitated and purified three times using n-heptane as solvent and ethanol as non-solvent to obtain oleic acid-stabilized ZnS nanomaterials.

[0059] (3) 10 g of 1-decyl DBU oleic acid ionic liquid and 10 g of ZnS nanomaterial were stirred and mixed at 80° C. for 2 h to obtain a lubricating oil composite additive.

[0060] Example 5

[0061] This embodiment provides a lubricating oil additive package, which is prepared by the following steps:

[0062] (1) Synthesis of 1-dodecyl DBU oleic acid ionic liquid: 0.1 mol DBU and 20 mL THF were added to a three-necked flask, and 0.11 mol dodecane bromide was slowly added dropwise at about 60°C. After the addition was complete, the temperature was raised to about 70°C and stirred for 8 hours. After the reaction was complete, the solvent was evaporated and the crude product was dissolved in 50 ml of distilled water. The product was then washed three times with ether, evaporated and dried under vacuum to obtain 1-dodecyl DBU bromide ionic liquid. The product was then reacted with sodium oleate to obtain 1-dodecyl DBU oleic acid ionic liquid.

[0063] (2) Synthesis of ZnS Nanomaterials: 0.4 mmol zinc acetate, 1 mL oleic acid, and 10 mL octadecene were placed in a three-necked flask and mixed at 120°C under vacuum for 30 min. The mixture was then heated to 280°C under an argon atmosphere. 0.4 mmol S in n-octylphosphine solution was injected into the reaction system and allowed to mature for 20 min. The mixture was then precipitated and purified three times using n-heptane as solvent and ethanol as non-solvent to obtain oleic acid-stabilized ZnS nanomaterials.

[0064] (3) 10 g of 1-dodecyl DBU oleic acid ionic liquid and 10 g of ZnS nanomaterial were stirred and mixed at 80° C. for 2 h to obtain a lubricating oil composite additive.

[0065] Application Example 1

[0066] The lubricating oil additive package prepared in Example 1 was added to the base oil PAO-6 in an amount of 0.05% by mass of the base oil PAO-6 to obtain lubricating oil 1.

[0067] Application Examples 2-5

[0068] The only difference from Application Example 1 is that the lubricating oil composite additive prepared in Example 1 is replaced by the lubricating oil composite additives in Examples 2-5 respectively.

[0069] Comparative Application Example 1

[0070] The only difference from Application Example 1 is that the lubricating oil additive package in Example 1 is not added, that is, only the base oil PAO-6 is used, which is a blank test.

[0071] Application Comparative Example 2

[0072] The only difference from Application Example 1 is that the lubricating oil additive package in Example 1 is not added, and only 1-octyl DBU oleic acid ionic liquid is added, with the added amount being 0.05% by mass of the base oil PAO-6.

[0073] Application Comparative Example 3

[0074] The only difference from Application Example 1 is that the lubricating oil composite additive in Example 1 is not added, and only oleic acid-stabilized ZnS nanomaterial is added, with the added amount being 0.05% of the mass of the base oil PAO-6.

[0075] Performance Testing

[0076] The coefficient of friction and wear spot diameter were measured using a four-ball tester. GCr steel balls with a hardness of 770 HV and a diameter of 12.7 mm were used. The test parameters were: load of 392 N, oil temperature of 75°C, and test duration of 60 minutes. The results are shown in Table 1.

[0077] Table 1

[0078]

[0079]

[0080] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method of this application and its core ideas. At the same time, for those skilled in the art, according to the ideas of this application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting this application, and the scope of protection of the present invention should be based on the scope defined by the claims. For those skilled in the art in this field, without departing from the spirit and scope of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the scope of protection of the present invention. Those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A novel lubricating oil composite additive, characterized in that: The lubricating oil composite additive comprises ionic liquid and metal compound nanomaterial; Wherein, the surface of the metal compound nanomaterial is connected with a long-chain fatty acid ligand.

2. The novel lubricating oil composite additive according to claim 1, characterized in that: The metal compound nanomaterials include ZnS nanomaterials, CuS nanomaterials, PbS nanomaterials, CuS nanomaterials, MoS2 nanomaterials, ZnO nanomaterials, CuO nanomaterials, and PbO nanomaterials; And / or, the long-chain fatty acid ligand is selected from fatty acid compounds having 10-24 carbon atoms; Preferably, the long-chain fatty acid ligand is selected from fatty acid compounds having 12-20 carbon atoms.

3. The novel lubricating oil composite additive according to claim 1, characterized in that: The ionic liquid includes 1,8-diazabicyclo[5.4.0]undec-7-ene salt ionic liquid; Preferably, the 1,8-diazabicyclo[5.4.0]undec-7-ene salt ionic liquid is a 1-alkyl DBU fatty acid ionic liquid, wherein the alkyl group is an alkyl group with 6-18 carbon atoms, and the fatty acid is an alkyl acid with 12-18 carbon atoms.

4. The novel lubricating oil additive package according to claim 1, characterized in that: The ionic liquid is selected from one or more of 1-octyl DBU oleic acid ionic liquid, 1-decyl DBU oleic acid ionic liquid, and 1-dodecyl DBU oleic acid ionic liquid; And / or, the mass ratio of the ionic liquid to the metal compound nanomaterial is 0.5-2:

1.

5. A method for preparing a novel lubricating oil composite additive, characterized in that: The following steps are involved: Step S1: Synthesis of ionic liquid: Add alkyl halide to DBU solution and heat to react. After the reaction is completed, an intermediate product 1 is obtained; then the intermediate product 1 is reacted with a fatty acid metal salt to obtain the ionic liquid; Step S2: Synthesis of metal compound nanomaterials: Add a soluble transition metal salt to a mixed solution of a long-chain fatty acid and a solvent, then stir the mixture at a first reaction temperature for a period of time under an inert gas atmosphere, then raise the temperature to a second reaction temperature, and then add a raw material A that precipitates the soluble transition metal salt. After the reaction is completed, the metal compound nanomaterial is obtained; Step S3: mixing the ionic liquid with the metal compound nanomaterial to obtain the lubricating oil composite additive; There is no particular order between step S1 and step S2.

6. The method for preparing the novel lubricating oil composite additive according to claim 5, characterized in that: In the step S1, the alkyl halide is selected from alkyl halide having 6 to 18 carbon atoms; Optionally, the alkyl halide is XR, wherein X is selected from F, Cl, Br, I, and R is selected from a C6-C18 alkyl group; And / or, the solvent of the DBU solution is selected from THF, acetone, dichloromethane, chloroform, tetrachloromethane, 1,2-dichloroethane; And / or, the fatty acid metal salt is selected from alkali metal salts of alkyl fatty acids having 6 to 18 carbon atoms; Optionally, the fatty acid metal salt is R1-COOM, wherein R1 is selected from a C11-C17 alkyl group, and M is selected from Li, Na, and K.

7. The method for preparing the novel lubricating oil composite additive according to claim 5, characterized in that: In step S1, the specific conditions of the heating reaction are: reaction temperature is 60-80°C, and reaction time is 6-10h; And / or, in the step S1, the molar ratio of the DBU to the alkyl halide is 1:1.1-1.2; And / or, the molar ratio of the intermediate product 1 to the fatty acid metal salt is 1:1-1.

2.

8. The method for preparing the novel lubricating oil composite additive according to claim 5, characterized in that: In step S2, the soluble transition metal salt is selected from soluble metal salts of zinc, soluble metal salts of copper, soluble metal salts of lead, and soluble metal salts of molybdenum; optionally, the soluble metal salt of zinc is selected from zinc acetate, zinc chloride, and zinc nitrate; the soluble metal salt of copper is selected from copper acetate, copper chloride, and copper nitrate; the soluble metal salt of lead is selected from lead acetate and lead nitrate; And / or, the long-chain fatty acid is selected from fatty acid compounds having 10 to 24 carbon atoms; and / or, the solvent is selected from aliphatic hydrocarbons having 10 to 24 carbon atoms; And / or, the raw material A is selected from n-octylphosphine solution of S, trioctylphosphine solution of S, triethanolamine, ethanolamine, ammonia water, NaOH, KOH; And / or, the metal compound nanomaterials include ZnS nanomaterials, CuS nanomaterials, PbS nanomaterials, CuS nanomaterials, MoS2 nanomaterials, ZnO nanomaterials, CuO nanomaterials, and PbO nanomaterials.

9. The method for preparing the novel lubricating oil composite additive according to claim 5, characterized in that: In step S2, stirring at the first reaction temperature for a period of time specifically comprises: stirring and reacting at 110-130° C. for 20-40 minutes; and / or, the second reaction temperature is 270-290°C; And / or, the molar ratio of the soluble transition metal salt to the raw material A is 1:1-2; And / or, in the step S3, the mass ratio of the ionic liquid to the metal compound nanomaterial is 0.5-2:1; the specific conditions for mixing the ionic liquid with the metal compound nanomaterial are: stirring and mixing at 70-90° C. for 1-3 hours.

10. A lubricating oil, characterized in that: Comprising a base oil and the novel lubricating oil composite additive as claimed in any one of claims 1 to 4, or comprising a base oil and the novel lubricating oil composite additive prepared by the preparation method as claimed in any one of claims 5 to 9; Preferably, the content of the novel lubricating oil composite additive in the lubricating oil is 0.01 wt% to 0.1 wt%.